The read aloud factor : how to create the habit that boosts your baby's brain - Rajan, Rekha S. (Parenting Press, 2023)
"We have always known that reading aloud is an important way to bond with your baby and develop language skills. Now neuroscience research is showing us the long-term benefit that reading aloud has for children-all the way into adulthood. Author Rekha S.Rajan was part of current research that shows individuals who were read to more frequently as children had a measurably healthier brain in old age. This innovative and accessible book incorporates the latest research on brain development, describes how reading aloud supports language and social-emotional development, and gives parents and caretakers what they need to make read alouds a regular and enjoyable part of the family routine"--